A proteome-wide screen identifies the calcium binding proteins, S100A8/S100A9, as clinically relevant therapeutic targets in aortic dissection - Jiang, Hui; Zhao, Yaping; Su, Meiming; Sun, Lu; Chen, Meijie; Zhang, Zhidan; Ilyas, Iqra; Wang, Zhihua; Little, Peter J.; Wang, Li; Weng, Jianping; Ge, Jianjun; et al. (Pharmacological research, 2024)
Aortic dissection (AD) is a fatal cardiovascular disease with limited pharmacotherapies. To discover novel therapeutic targets for AD, the present study was conducted on ascending aorta samples from AD patients versus those from control subjects using proteomic analysis. Integrated proteomic data analysis identified S100 calcium-binding proteins A8 and A9 (S100A8/A9) as new therapeutic targets for AD. As assessed by ELISA, the circulating levels of S100A8/A9 were elevated in AD patients. In addition, we validated the upregulation of S100A8/A9 in a mouse model of AD. In vitro and in vivo studies substantiated that S100A8/A9, as danger-associated molecular pattern molecules, promotes the smooth muscle cells phenotypic switch by inhibiting serum response factor (SRF) activity but elevating NF-κB dependent inflammatory response. Depletion of S100A8/A9 attenuates the occurrence and development of AD. As a proof of concept, we tested the safety and efficacy of pharmacological inhibition of S100A8/A9 by ABR-25757 (paquinimod) in a mouse model of AD. We observed that ABR-25757 ameliorated the incidence of rupture and improved elastin morphology associated with AD. Further single-cell RNA sequencing disclosed that the phenotypic switch of vascular smooth muscle cells (VSMCs) and inflammatory response pathways were responsible for ABR-25757-mediated protection against AD. Thus, this study reveals the regulatory mechanism of S100A8/A9 in AD and offers a potential therapeutic avenue to treat AD by targeting S100A8/A9.